Evaluasi Pemanfaatan Zonasi TPA Tamangapa Kota Makassar - Andi Ike Nurjannah; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
Makassar City Tamangapa Landfill is one of the crucial infrastructures, but its management is neglected so that it requires serious handling. This study aims to determine the existing conditions of each zoning utilization and the direction of sustainable zoning utilization. The analytical method used is descriptive and quantitative evaluation criteria analysis using a comparative method between existing and ideal conditions which is then weighted, spatial analysis consisting of proximity and superimpose analysis. The results of the analysis show that the Tamangapa landfill zoning utilization as a whole is included in the